(3JPjjd CQLhRI GHf SjfG aj GdMejGJs - (3CHi ehSi gGQhf Hf ESMGb Hf YRQhfs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdbGOQ GdOGFe GdaQO GdMcje GdaGWQ hgPg CQLhRI fXeJgG hai VQhH GdMejGJ UaJgG s
(3BNQgG (B:s
(3hGSJYed GdJMdjd eG GSJWYfG Jcf HgPG GdaYd bO CUHfG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B191 - (3U(B193s
(3HgG BKGQ JeRjbs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs